DIGITIZATION OF VAT – E-INVOICING AND CLEARANCE SYSTEM AS A MODEL - Zaiets, Oleksandr (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to study the features of the European experience in using electronic invoices, regarding the electronic administration of value added tax and the practical implementation of electronic invoices in Ukraine. From January 1, 2019, the European Union (Italy) introduced the requirement for electronic invoicing. Companies must create electronic invoices for B2G, B2B and B2C sales and send them to the invoice recipient in a defined XML format through a central platform. This allows the tax authorities to exercise control, which significantly reduced the VAT gap in the first few months after its introduction. Research methods: the study is based on general scientific methods as well as specific legal methods, with the help of which various scientific positions and doctrinal approaches to the development of ideas regarding understanding the concept and essence of legal fictions, as well as their significance in legal sphere, have been analyzed. Results: Ukraine still lags behind in using such digital opportunities. In order to combat fraud and reduce compliance costs for companies, the introduction of mandatory and largely standardized electronic invoicing with a central transmission platform should be considered. This is especially true for B2B sales. In addition, the complex standardized exchange of invoices creates huge opportunities for automating processes in the field of accounting. Discussion: the inclusion of B2C transactions should be analyzed in more detail. In any case, attention should be paid to (at least) nationwide implementation, which should be well prepared and early involvement of all involved actors. Ukraine must decide how it wants to respond to this development. Given the pioneering role of the EU. It turns out that the Italian registration procedure with mandatory electronic invoicing sets the course for digital VAT and can therefore be used as a blueprint for a possible Ukrainian system. The article describes the legal history of the origin of the Italian system and explains its functionality in more detail. It covers the creation of bound companies and shows how you can create, send and receive e-invoices. The Italian experience is examined for its transferability to Ukraine: what opportunities and risks exist for the administration and companies after implementation and what points are relevant after implementation.